Formulation of an antimicrobial hydrogel using Psidium guagava L. leaves extract through radiation crosslinking technology - Arienza, Mariane Allen J.; Santos, Martin Rey Edrick C.; Tada, Benjamin II D.
Hydrogels are one of the most common dosage forms in skin formulations. There are different methods of formulating a hydrogel and one of which is through crosslinking with the use of gamma radiation. Guava leaves extract (Psidium guajava) was used as the active ingredient. The excipients were polyvinylpyrrolidone (PVPK90), polyethylene glycol (PEG-400), benzylkonium chloride, and agar-agar. Mixing while heating was done prior to irradiation with the dose of 25 kilogray. Quality control tests such as organoleptic properties, pH, gel fraction, compression test, and antimicrobial property against Staphylococcus aureus were performed before and after irradiation. The optimal formulation was determined and through quality control tests, the cross-linked hydrogel was found to be slightly acidic. The cross-linking was also found to be significantly effective through the compression test and gel fraction. Cross-linking through radiation technology was shown to be an effective way of formulating a hydrogel patch incorporated with P. guajava L.